Spatial- and temporal-interpolations for efficient hybrid wave numerical simulations - Shen, Hao; Tang, Xiaotian; Lyu, Chao; Zhao, Liang (Frontiers in Earth Science, 2022)
The hybrid wave forward simulation is the basic technology of full-wave inversion for imaging the localized multi-scale structure by constraining the inversion in a region. In this study, we quantitatively discuss the error of the hybrid method and propose an efficient hybrid method for improving accuracy and decreasing memory demand. In the time domain, we introduce the Fourier interpolation method which allows recovering the sparsely stored hybrid inputs with smaller error (about three orders of magnitude) than the traditional method. In the spatial domain, when the meshing of the global and hybrid simulations differs, we propose the multi-elements spline interpolation method using more polydirectional interpolated points that can appreciably reduce the relative error of the hybrid method caused by inaccurate hybrid inputs. We compare the accuracy of the proposed methods to traditional interpolation methods in both 2D and 3D cases and the results show that our new methods are preferable.